Treatment of low back pain: First extended follow up of an original trial (NCT00600197) comparing a multidisciplinary group‐based rehabilitation program with oral drug treatment alone up to 24 months. (10th October 2014) - Tavafian, Sedigheh Sadat; Jamshidi, Ahmad Reza; Shay, Barbara
Abstract: Background: This study aimed to examine the effects of the extended follow‐up of an original trial (NCT00600197) which has been published in The Clinical Journal of Pain . Methods: Eighty‐three percent (165 of 197) of the original study, including 82 patients in intervention and 83 patients in the control group, provided extended 24‐month follow‐up data. The intervention was a group‐based multidisciplinary rehabilitation program which was continued by monthly motivational consultation. Data on measures of Short Form 36 (SF‐36), Quebec Disability Scale (QDS) and Ronald Morris Disability (RDQ) were collected at 12‐, 18‐ and 24‐month follow‐ups and analyzed through repeated measures analysis of variance. Results: The patients who responded ( n  = 165) and who did not respond ( n  = 32) to the questionnaires were the same in terms of all baseline data except for physical function which was better for respondents ( P  <   0.05). Among the respondents, both intervention and control groups were the same at baseline except for education level and mental health which was better in the intervention group ( P  <   0.05). As a result, the intervention group had consistently better outcomes regarding all variables except for social function at all follow‐up times. Furthermore, in the intervention group only for mental health the interaction between time and group was significant ( P  = 0.01). Discussion: The designed multidisciplinary program could improve health‐related quality of life and disability up to 24 months in chronic low back pain patients.